Kedudukan Suami Menurut Hukum Waris Bali dalam Perkawinan Nyeburin di Desa Adat Peliatan Ubud Gianyar - Cokorda Gde Yudha Putra; I Made Suwitra; Gayatri Sudibya (Jurnal Konstruksi Hukum, 2021)
Balinese men are the successors of the lineage / continuation of the future of the family so that a family continues to have descendants and does not experience extinction. However, these hopes cannot come true if the married couple cannot give birth to a son or even have no children or offspring at all. The purpose of this study was to determine the law of Balinese inheritance in nyeburin marriages in the traditional village of Peliatan. The formulation of the problem in this study is what is the position of the husband in the Nyeburin marriage according to the Awig-Awig of the Peliatan Traditional Village and the factors that encourage the implementation of the Nyeburin marriage in the Peliatan Traditional Village. The type of research used is empirical using a sociological approach, statutory approach, conceptual, case and customary law approaches. The data sources obtained from this research are primary data from interviews and observations and secondary data from Awig-awig traditional villages, legislation and related research. The results of the research include the husband's position as predana in intermarriage according to the Awig-Awig of the Peliatan Traditional Village, if the marriage breaks either those who still live at their wife's house or who have returned to their original home (mulih deha / truna), no one has explicitly regulated in positive rule of law. The factors that encourage the implementation of the Nyeburin marriage in the Peliatan Traditional Village are due to the request of the woman's parents due to not having a son and only having a daughter, a factor that comes from the male side (as predana), namely because of mutual love between the two both sides.